Impairment, disability, social support and depression among older parents in rural Thailand - S. Suttajit (2018)
Background It is not known whether social support modifies the association between depression and impairment or disability in older people from developing countries in Asia. Method We used a Thai version of the EURO-D scale to measure depression in 1104 Thai rural community-dwelling parents aged 60 years. These were all those providing data on depression who were recruited as part of a study of older adults with at least one living child (biological, stepchild or adopted child). Logistic regression modelling was used to determine: (a) whether impairment, disability and social support deficits were associated with depression; (b) whether social support modified this association. Results There were strong graded relationships between impairment, disability, social support deficits and EURO-D caseness. Level of impairment, but not disability, interacted with poor social support in that depression was especially likely in those who had more physical impairments as well as one or more social support deficits (p value for interaction=0.018), even after full adjustment. Conclusions Social support is important in reducing the association between physical impairment and depression in Thai older adults, especially for those with a large number of impairments. Enhancing social support as well as improving healthcare and disability facilities should be emphasized in interventions to prevent depression in older adults. © Cambridge University Press 2010.